2019
DOI: 10.1111/tpj.14539
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of kernel nutritional traits during maize domestication and improvement

Abstract: Summary The nutritional traits of maize kernels are important for human and animal nutrition, and these traits have undergone selection to meet the diverse nutritional needs of humans. However, our knowledge of the genetic basis of selecting for kernel nutritional traits is limited. Here, we identified both single and epistatic quantitative trait loci (QTLs) that contributed to the differences of oil and carotenoid traits between maize and teosinte. Over half of teosinte alleles of single QTLs increased the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 79 publications
3
29
0
Order By: Relevance
“…Structural variation in the identified genetic regions also merits further examination. A mutator distance-relative transposable element (TE) in the first intron of maize dxs2 was recently identified to affect expression of dxs2, which was in turn positively correlated with total carotenoid content (FANG et al 2020). This TE had been present in teosinte; appears to have been subject to selection during maize domestication and improvement; and was found to be nearly fixed in the yellow-grain maize lines examined.…”
Section: Epistasis Between Identified Genesmentioning
confidence: 99%
“…Structural variation in the identified genetic regions also merits further examination. A mutator distance-relative transposable element (TE) in the first intron of maize dxs2 was recently identified to affect expression of dxs2, which was in turn positively correlated with total carotenoid content (FANG et al 2020). This TE had been present in teosinte; appears to have been subject to selection during maize domestication and improvement; and was found to be nearly fixed in the yellow-grain maize lines examined.…”
Section: Epistasis Between Identified Genesmentioning
confidence: 99%
“…All the three husk traits in the MX population exhibited a broad range of phenotypic variation with normal distribution. The genetic analysis showed that the heritability of three husk traits is fairly high, indicative of superior genetic effect in this population studied [ 33 ]. In addition, except for environment variation, none of significant difference were detected in genetic or interaction between genetic and environment within RILs.…”
Section: Discussionmentioning
confidence: 99%
“…The evolutionary trajectories of the genes or QTLs responsible for variations in oil and carotenoid traits revealed that these traits caused diverse selection events during maize domestication. This indicates the complex selection patterns of the genes that underlie maize kernel nutritional traits and shows that teosinte alleles can also be valuable for improving those traits ( Fang et al., 2020 ).…”
Section: The Origin Evolution and Natural Variation Of Maize Through A Metabolomic Lensmentioning
confidence: 99%